Paternalism: An Analysis. Issue 2 (20th July 2015) - RYAN, SHANE
Abstract : In this article I argue for a particular analysis of paternalism. I start by examining Dworkin's conditions for the paternalist act and make a case for alternative conditions. I argue that the paternalist actor acts irrespective of what she believes the wishes of the target of her action are and the paternalist actor acts because she has a positive epistemic standing that the act may or will improve the welfare of the target of her action. I also argue that it is consistent with my analysis that there are paternalist acts that don't interfere with the autonomy of the object of the paternalist act. I describe some such acts and make the case that such acts, when they are paternalist acts, may be morally permissible and outline the factors that bear on their permissibility. Finally I locate my analysis in the literature by comparing it to a number of other accounts.